Substrate Stress‐Relaxation Regulates Scaffold Remodeling and Bone Formation In Vivo. Issue 1 (20th December 2016) - Darnell, Max; Young, Simon; Gu, Luo; Shah, Nisarg; Lippens, Evi; Weaver, James; Duda, Georg; Mooney, David
Abstract : The rate of stress relaxation of adhesion substrates potently regulates cell fate and function in vitro, and in this study the authors test whether it can regulate bone formation in vivo by implanting alginate gels with differing rates of stress‐relaxation carrying human mesenchymal stem cells into rat calvarial defects. After three months, the rats that received fast‐relaxing hydrogels ( t 1/2 ≈ 50 s) show significantly more new bone growth than those that received slow‐relaxing, stiffness‐matched hydrogels. Strikingly, substantial bone regeneration results from rapidly relaxing hydrogels even in the absence of transplanted cells. Histological analysis reveals that the new bone formed with rapidly relaxing hydrogels is mature and accompanied by extensive matrix remodeling and hydrogel disappearance. This tissue invasion is found to be prominent after just two weeks and the ability of stress relaxation to modulate cell invasion is confirmed with in vitro analysis. These results suggest that substrate stress relaxation can mediate scaffold remodeling and thus tissue formation, giving tissue engineers a new parameter for optimizing bone regeneration. Abstract : The stress relaxation of a cell's adhesion substrate is shown to influence its behavior. In this work, the stress relaxation of implanted hydrogels is shown to influence bone healing by modulating the ability of cells to remodel the matrix. These results are expected to have implications for the optimization of bone regeneration constructs.